Dose response and architecture in volume staged radiosurgery for large arteriovenous malformations: A multi-institutional study. (March 2020) - Seymour, Zachary A.; Chan, Jason W.; Sneed, Penny K.; Kano, Hideyuki; Lehocky, Craig A.; Jacobs, Rachel C.; Ye, Hong; Chytka, Tomas; Liscak, Roman; Lee, Cheng-Chia; Yang, Huai-che; Ding, Dale; et al.
Highlights: Margin dose per volume stage and compact architecture are favorable in terms of response with VS-SRS. Diffuse nidus architecture is associated with a threshold dose of 17 Gy for response. Dose escalation for compact nidus architecture may improve rates of cure as well. Future efforts should evaluate continued dose escalation with smaller volumes per volume-stage. Abstract: Background: Optimal treatment paradigm for large arteriovenous malformations (AVMs) is controversial. Volume-staged stereotactic radiosurgery (VS-SRS) provides an effective option for these high-risk lesions, but optimizing treatment for these recalcitrant and rare lesions has proven difficult. Methods: This is a multi-centered retrospective review of patients treated with a planned prospective volume staging approach to stereotactically treat the entire nidus of an AVM with volume stages separated by intervals of 3–6 months. A total of 9 radiosurgical centers treated 257 patients with VS-SRS between 1991 and 2016. We evaluated near complete response (nCR), obliteration, cure, and overall survival. Results: With a median age of 33 years old at the time of first SRS volume stage, patients received 2–4 total volume stages and a median follow up of 5.7 years after VS-SRS. The median total AVM nidus volume was 23.25 cc (range: 7.7–94.4 cc) with a median margin dose per stage of 17 Gy (range: 12–20 Gy). Total AVM volume, margin dose per stage, compact nidus, lack of prior embolization, and lack of thalamic location involvement were all associated with improved outcomes. Dose >/= 17.5 Gy was strongly associated with improved rates of nCR, obliteration, and cure. With dose >/= 17.5 Gy, 5- and 10-year cure rates were 33.7% and 76.8% in evaluable patients compared to 23.7% and 34.7% of patients with 17 Gy and 6.4% and 20.6% with <17 Gy per volume-stage ( p  = 0.004). Obliteration rates in diffuse nidus architecture with <17 Gy were particularly poor with none achieving obliteration compared to 32.3% with doses >/= 17 Gy at 5 years ( p  = 0.007). Comparatively, lesions with a compact nidus architecture exhibited obliteration rates at 5 years were 10.7% vs 9.3% vs 26.6% for dose >17 Gy vs 17 Gy vs >/=17.5 Gy. Conclusion: VS-SRS is an option for upfront treatment of large AVMs. Higher dose was associated with improved rates of nCR, obliteration, and cure suggesting that larger volumetric responses may facilitate salvage therapy and optimize the chance for cure.